IMPLEMENTASI PEMBELAJARAN MATA KULIAH PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL, SPIRITUAL, DAN SOSIAL MAHASISWA STTI BONTANG - Irianto; Arianto Al-Hikma, M. Rizky; Anggataruna, Reza (Manajemen Pendidikan Program Doktor, 2022)
The role of Islamic religious education is very crucial for students, this is because Islamic religious learning teaches about morals and morals. Morals and morals are very important because they will be useful in everyday life. In addition, Islamic religious education also teaches emotional, spiritual, and social intelligence. In this study, it will be discussed how the implementation of Islamic religious education in improving emotional, spiritual, and social intelligence for Bontang Technology College students. The result of this research show that the implementation of Islamic lecturing in developing emotional, spritual and social intellegence for students of STTI Bontang is very good.